Human adipose‐derived cells can serve as a single‐cell source for the in vitro cultivation of vascularized bone grafts. (17th August 2012) - Correia, Cristina; Grayson, Warren; Eton, Ryan; Gimble, Jeffrey M.; Sousa, Rui A.; Reis, Rui L.; Vunjak‐Novakovic, Gordana
Abstract Orthopaedic surgery often requires bone grafts to correct large defects resulting from congenital defects, surgery or trauma. Great improvements have been made in the tissue engineering of bone grafts. However, these grafts lack the vascularized component that is critical for their survival and function. From a clinical perspective, it would be ideal to engineer vascularized bone grafts starting from one single‐cell harvest obtained from the patient. To this end, we explored the potential of human adipose‐derived mesenchymal stem cells (hASCs) as a single‐cell source for osteogenic and endothelial differentiation and the assembly of bone and vascular compartments within the same scaffold. hASCs were encapsulated in fibrin hydrogel as an angioinductive material for vascular formation, combined with a porous silk fibroin sponge to support osteogenesis, and subjected to sequential application of growth factors. Three strategies were evaluated by changing spatiotemporal cues: (a) induction of osteogenesis prior to vasculogenesis; (b) induction of vasculogenesis prior to osteogenesis; or (c) simultaneous induction of osteogenesis and vasculogenesis. By 5 weeks of culture, bone‐like tissue development was evidenced by the deposition of bone matrix proteins, alkaline phosphatase activity and calcium deposition, along with the formation of vascular networks, evidenced by endothelial cell surface markers, such as CD31 and von Willebrand factor, and morphometric analysis. Most robust development of the two tissue compartments was achieved by sequential induction of osteogenesis followed by the induction of vasculogenesis. Taken together, the collected data strongly support the utility of hASCs as a single‐cell source for the formation of vascularized bone tissue. Copyright © 2012 John Wiley & Sons, Ltd.